Investigation of Nitrate Removal from Aqueous Solutions by Egg Shell Nanostructure Adsorbent - Ali Bafkar; Neda Babeli (محیط زیست و مهندسی آب, 2019)
Pollution of groundwater and surface water into nitrate in many parts of the world is a serious problem. Nitrate can cause Eutrophication water sources and related problems. The creation of adverse health effects on aquatic ecosystems is one of the adverse effects of high concentrations of nitrate in aqueous solutions. The aim of this study was to investigate the possibility of using egg shell as a low-cost adsorbent in removal of nitrate from aqueous solutions. In this study, the effects of factors such as pH, adsorbent mass, contact time and initial concentration of nitrate were studied. Isotherm models (Langmuir and Freundlich) and kinetic models (Lagergren and Ho and colleagues) were used to examine the adsorption process. The results showed that for the adsorbent, the balance time after 30 minutes and maximum nitrate adsorption at pH=5 were obtained. By increasing the adsorbent mass from 0.3 to 0.5 gram, the removal efficiency increased from 96.01 to 97.24 percent, but with an increase in adsorbent content from 0.5 to 1.6 gram, there was a significant difference in the adsorption efficiency Failed. By increasing the concentration of dissolved nitrate (5.120 mg/l), the removal efficiency decreased from 99.42 to 87.38%. Based on the results, the adsorption process was followed by the model of Ho (Pseudo second order kinetics), and the adsorption data was more consistent with Freundlich isotherm. The results of this study showed that egg shell nanostructure adsorbent has high potential for removal of nitrate ions from aqueous solutions.